Urban Formations of Multi-story Housing in Compact City Comparison with the Local Reality in Damascus - فاكوش تمام; الصواف ريم (Latakia University Journal -Engineering Sciences Series, 2021)
Increasing population growth rates is a constant concern of governments and has a great influence on their policies all over the world, given the challenges that accompany them at the economic, environmental, and on the socio-urban levels and the consequent urban expansion and erosion of green areas which all had its clear reflection on entire cities. This research discusses the concept of the compact city, which was recently highlighted by international organizations and academic research groups and its role in facing the challenges as one of the proposals in finding effective and what applies to the urban and architectural reality of urban communities represented by the multi-story housing by reviewing its urban characteristics spatiality and their effect on shaping the city and the urban forms of its multi-story housing.